Laser-induced breakdown spectroscopy (LIBS), part II: review of instrumental and methodological approaches to material analysis and applications to different fields - Hahn, David W; Omenetto, Nicoló (Applied spectroscopy, 2012)
The first part of this two-part review focused on the fundamental and diagnostics aspects of laser-induced plasmas, only touching briefly upon concepts such as sensitivity and detection limits and largely omitting any discussion of the vast panorama of the practical applications of the technique. Clearly a true LIBS community has emerged, which promises to quicken the pace of LIBS developments, applications, and implementations. With this second part, a more applied flavor is taken, and its intended goal is summarizing the current state-of-the-art of analytical LIBS, providing a contemporary snapshot of LIBS applications, and highlighting new directions in laser-induced breakdown spectroscopy, such as novel approaches, instrumental developments, and advanced use of chemometric tools. More specifically, we discuss instrumental and analytical approaches (e.g., double- and multi-pulse LIBS to improve the sensitivity), calibration-free approaches, hyphenated approaches in which techniques such as Raman and fluorescence are coupled with LIBS to increase sensitivity and information power, resonantly enhanced LIBS approaches, signal processing and optimization (e.g., signal-to-noise analysis), and finally applications. An attempt is made to provide an updated view of the role played by LIBS in the various fields, with emphasis on applications considered to be unique. We finally try to assess where LIBS is going as an analytical field, where in our opinion it should go, and what should still be done for consolidating the technique as a mature method of chemical analysis.